THE EFFECT OF MASSAGE ON SERUM BILIRUBIN LEVELS AND NEONATUS BODY WEIGHT WITH PHOTOTHERAPY - Murtiningsih, Murtiningsih; Syam, Mayrita (Journal of Maternity Care and Reproductive Health, 2023)
Approximately 25-50% of newborns experience physiological hyperbilirubinemia in the first week of life, 80% occur in premature babies and 60% in full-term babies. Hyperbilirubinemia can be toxic and dangerous, such as encephalopathy. At Ummi Hospital, Bogor, the number of babies born from January to April 2021 was 704, and 11.4% had hyperbilirubinemia and no baby massage intervention had been carried out. Massage for newborns with hyperbilirubinemia reduces bilirubin levels and increases the baby's weight. This study aims to find out whether massage can reduce serum bilirubin levels and increase the weight of hyperbilirubinemia babies who receive phototherapy. This research was conducted in the perinatology room at Ummi Hospital, Bogor, Indonesia with ethical permit no. 02/KEPK/X/2021. The research design used a quasi-experimental pretest-posttest with a control group design, with a sample of 40 hyperbilirubinemia babies. After analysis using the dependent t-test and independent t-test, the results of the study showed that there was no significant difference between body weight before the intervention and after the intervention with p > 0.05 in the intervention group (p=0.054) and the control group (p =0.286). There was a significant difference in bilirubin levels (p<0.05) before and after the intervention in both the intervention group and the control group (p=0.001). Conclusion: Phototherapy alone or combined with massage can reduce serum bilirubin levels in babies. Adding massage to provide comfort to the baby and other benefits.